Model for probabilistic assessment of oil outflow event caused by tanker accident - Česnauskis, Mindaugas (Transport, 2007)
Model proposed in this paper can be used to predict oil outflow event, caused by the tanker accident, probability distribution in different sectors of navigation area. The use of expert judgment techniques to obtain necessary data for application of the model ensures that all relevant available information (world and regional marine accident statistics, factors inherent to navigational area in question) will be duly taken into account. Model is designed for the Lithuanian responsibility sea area; the assessment of probability of oil outflow event and its distribution in different sectors of the area is performed.First Published Online: 27 Oct 2010